Comprehension of Online Informed Consents: Can It Be Improved?. Issue 3 (2nd April 2016) - Duvall Antonacopoulos, Nikolina M.; Serin, Ralph C.
Abstract : This study examined possible ways to ensure that participants provide fully informed consent for online surveys. Participants were randomly assigned to read either a traditional informed consent or one of three modified versions: enhanced (e.g., images, bullet points), consent for each key element, or a combination of these two. Those who read the combination version scored higher on a comprehension quiz, guessed at fewer questions, and were more likely to read all of the informed consent than those who received the traditional version. These findings suggest that comprehension can be improved by adopting alternatives to the traditional informed consent.